Differential interaction between two Glomus intraradices strains and a phosphate solubilizing bacterium in maize rhizosphere - Fernandez Bidondo, Laura (2012)
Arbuscular mycorrhizal (AM) fungi and phosphate solubilizing bacteria (PSB) have a positive effect on plant productivity primarily through increasing phosphate availability. In order to study the interaction between AM fungi and PSB, we used Bacillus megaterium, a PSB isolated from the sterilized surface of AM germinated spores, and two strains of the AM fungus Glomus intraradices with different mycelial architecture. A greenhouse experiment was designed with maize as host plant with the addition of tribasic calcium phosphate. We tested the hypothesis that PSB, intimately linked with AM fungi, could interact differentially with the two AM strains. We concluded that inoculation with the PSB positively affected maize mycorrhization. Insoluble phosphate alone did not influence the AM extraradical mycelium (ERM)length and maize mycorrhization when bacteria were not inoculated. The results provide evidence that the adverse effect on infectivity for some AM strains might be caused by solubilized phosphorus release tothe rhizosphere by PSB. Differences related to the mycelium architecture of each AM strain were observed: the density of PSB in rhizosphere soil was significantly higher only with the GA8 strain coinciding with the highest values of maize biomass. The density of bacteria associated with GA8 mycelium could be the result of the transfer of photosynthates through the rhizosphere; this close contact would favor the persistence of the intimate relationship between PSB and AM hyphae. In the bacteria-free treatments,soil adherence was not significantly altered. Although the highest development of ERM occurred with GA5, plants inoculated with GA8 showed the highest values for soil adherence. This may be due to the AM mycelium which modifies bacterial persistence in the rhizosphere and consequently soil adherence. Our results show that for potential applications, some characteristics of the AM strains are key in the selection of the AM fungi?PSB combinations. These include the tolerance to soluble phosphorus, the rate of root colonization, and ERM development that favors the persistence of bacteria in rhizosphere soil.